EFFECT OF INDUCED POLYPLOIDY ON PLANT GROWTH, CHLOROPHYLL AND FLAVONOID CONTENT OF ARTEMISIA CINA - Kasmiyati, Sri; Kristiani, Elizabeth Betty Elok; Herawati, Maria Marina (Biosaintifika: Journal of Biology & Biology Education, 2020)
Artemisia cina is one of a member of genus Artemisia that has potential as a medicinal plant. However, the levels of Artemisia medicinal bioactive compounds are very low. Polyploidization is an alternative method that can enhance of growth and secondary metabolite productions of plants. The aims of this research were to determine the effect of polyploid induction using colchicine and plant growth regulator toward plant growth, the chlorophyll, kaemferol and quercetin contents of A. cina. Four different A. cina used in this research consisted of two diploid genotypes (TWN and KJT) and two polyploid genotypes (J and M). Induction of mutant polyploid was conducted using colchicine and combination of plant growth regulator benziladenyl (BA) and 2,4-dichlorophenoxyacetic acid (2,4-D). The measured plant growth parameters were dry weight, leaf area, and plant height. The chlorophyll content of leaves was determined spectrophotometrically, and flavonoid content determined using HPLC. The result showed that the polyploid genotype (M) significantly decreased leaf and root growth compared to the KJT and TWN. In A. cina plants, polyploidization using colchicine is more effective in increasing the biomass than using combination plant growth regulator BA and 2,4-D. The flavonoid content of KJT was the lowest, and significantly different compared to the other plants. This study provides new information about the effect of polyploid on growth and flavonoid content in A. cina. This can be  useful information to develop A. cina to become a medicinal plant.